2016
DOI: 10.1186/s40409-016-0068-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival of a newborn from a pregnant woman with rabies infection

Abstract: BackgroundRabies is very common in People’s Republic of China. Each year thousands of people die because of this disease, but rabies diagnosed in pregnancy is very rare.Case PresentationIn this study, we report the case of a pregnant woman who was infected with the rabies virus after a dog bite. The symptoms of rabies appeared in labor and she died after pregnancy. Her baby and husband did not develop the disease.ConclusionThe phenomenon that the newborn infant was healthy may be related to the protective role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A growing body of literature documents peripartum rabies cases. Including the six cases reported here, case reports and a literature review found 20 documented probable or suspected peripartum rabies cases reported during the 114-year period, 1902–2016 ( 8 , 9 ). A total of 17 neonates survived, and were reported to be healthy, including eight who did not receive vaccine or immunoglobulin after caesarean or vaginal delivery ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature documents peripartum rabies cases. Including the six cases reported here, case reports and a literature review found 20 documented probable or suspected peripartum rabies cases reported during the 114-year period, 1902–2016 ( 8 , 9 ). A total of 17 neonates survived, and were reported to be healthy, including eight who did not receive vaccine or immunoglobulin after caesarean or vaginal delivery ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine transmission is the spread of the rabies virus from mother to fetus via the placenta (Qu et al, 2016). Even though rabies is rare to transmit through the intrauterine route, a few cases reported and described raise the possibility (Scheidegger 1953).…”
Section: Intrauterine Transmissionmentioning
confidence: 99%